Waisted : a novel - Meyers, Randy Susan (Atria Books, 2019)
Agreeing to become documentary subjects in their desperation to lose weight, two successful working moms, each struggling with family discrimination, discover self-love and sisterhood while plotting against the exploitative creators of their show.